Normal-temperature spraying type super-hydrophobic friction electricity durable coating composition and preparation method thereof

By developing a method for preparing a room-temperature spray-applied superhydrophobic triboelectric durable coating composition, the high cost and performance degradation issues of TENG devices in smart city applications have been solved. This method enables the preparation of high-performance, durable superhydrophobic surfaces, which are suitable for the large-scale production of triboelectric nanogenerators.

CN120924103APending Publication Date: 2025-11-11SHANDONG UNIV SHENZHEN RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511101873.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing triboelectric nanogenerators (TENGs) face challenges in large-scale deployment and application in smart cities, including high costs, difficulty in mass production, mechanical wear, and chemical corrosion. Furthermore, superhydrophobic surface preparation technology has limitations in large-area uniform coating and complex substrate processing, leading to rapid performance degradation.

Method used

A high-performance superhydrophobic triboelectric durable coating is prepared using a room-temperature sprayable superhydrophobic triboelectric durable coating composition, including fluoropolymers, nanoparticles and dispersants, through high-pressure airless spray guns, 3D scanning technology and microwave radiation. Combined with ultrasonic cleaning and plasma cleaning equipment, the coating quality and adhesion are ensured.

Benefits of technology

It significantly improves triboelectricity and superhydrophobicity, simplifies the fabrication process, facilitates large-scale production, enhances device durability and performance stability, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120924103A_ABST
    Figure CN120924103A_ABST
Patent Text Reader

Abstract

The invention discloses a normal-temperature spraying type super-hydrophobic triboelectric durable coating composition and a preparation method thereof, a production raw material formula comprises an effective component and a polar organic solvent, and the mass ratio of the polar organic solvent to the effective component is (6-10): 1; the effective components comprise a fluorine-containing polymer, nanoparticles and a dispersing agent; the mass ratio of the fluorine-containing polymer to the modified nanoparticles is (8-12): 1; and the dispersant accounts for 0.5-1.5% of the mass of the effective components. The method has the advantages that the triboelectricity and the super-hydrophobicity of the electric durable coating formed by spraying can be remarkably improved, the curing time is shortened, the production efficiency is improved, operation is easy and convenient, parameters are clear, control and large-scale production are convenient, various materials are selected, different requirements can be met, and the stability of a mixed solution can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface coating technology, and in particular to a production technology for superhydrophobic triboelectric durable coatings. Background Technology

[0002] With the rapid development of smart city construction, more and more advanced sensing and energy harvesting technologies are being applied to urban environmental monitoring, traffic management, human-computer interaction and other fields. Among them, triboelectric nanogenerators (TENGs) have shown great application potential in self-driven sensing and energy harvesting due to their unique electromechanical conversion mechanism and excellent performance. TENGs utilize the principles of contact electrification and electrostatic induction to directly convert mechanical energy into electrical energy through contact friction and charge transfer between the surfaces of two materials. In recent years, researchers have successfully achieved highly sensitive sensing of solid-liquid and solid-solid interface contact states and efficient harvesting and utilization of environmental mechanical energy by designing and modifying the surface morphology and chemical composition of TENG devices. A series of self-driven sensors and energy harvesting devices based on TENGs have been developed and applied in scenarios such as road condition monitoring, structural health diagnosis and wearable devices in smart cities.

[0003] The introduction of superhydrophobic surfaces can significantly improve the performance of triboelectric generators (TENGs). On the one hand, based on high surface roughness, superhydrophobic surfaces can increase the triboelectric charge density, thereby improving the electrical output performance of solid-solid TENGs. On the other hand, superhydrophobic surfaces have a repulsive effect on liquids, which can, to some extent, suppress the degradation of TENG electrical output performance in humid environments, achieving high-performance triboelectric generation at the solid-liquid interface. Therefore, the fabrication of high-performance superhydrophobic surfaces has become a key to the development of efficient TENGs. However, existing TENGs still face many technical challenges in large-scale deployment and application in smart cities. First, the fabrication of high-performance TENGs often involves complex micro-scale processes. Nanofabrication or surface modification treatments are costly and difficult to scale up, limiting the mass production and widespread application of devices. Secondly, factors such as mechanical wear, chemical corrosion, and dirt and dust commonly found in urban environments can easily lead to rapid performance degradation of TENG devices, making it difficult to ensure their long-term stable operation. In addition, commonly used superhydrophobic surface preparation techniques such as etching, template methods, solution immersion methods, and electrochemical deposition methods are insufficient in achieving large-area uniform coating and complex substrate processing. Therefore, developing a simple, efficient, and scalable superhydrophobic surface preparation technology is crucial for realizing the mass production of high-performance TENG devices and their large-scale application in smart cities. Summary of the Invention

[0004] To improve the triboelectric properties and superhydrophobicity of superhydrophobic triboelectric durable coatings, this invention provides a room-temperature sprayable superhydrophobic triboelectric durable coating composition and its preparation method.

[0005] The technical solution adopted in this invention is: a method for preparing a room-temperature sprayable superhydrophobic triboelectric durable coating composition. The raw material formulation includes an active ingredient and a polar organic solvent, wherein the mass ratio of the polar organic solvent to the active ingredient is 6-10:1; the active ingredient includes a fluoropolymer, nanoparticles, and a dispersant; the mass ratio of the fluoropolymer to the nanoparticles is 8-12:1; and the dispersant accounts for 0.5%-1.5% of the mass of the active ingredient.

[0006] The polar organic solvent used in this invention can be selected from one or any combination of ethyl acetate, acetone, ethanol, FC40 electronic fluorinated liquid, n-propanol, methyl isobutyl ketone, N,N-dimethylformamide, methyl ethyl ketone, and xylene.

[0007] As will be readily understood by those skilled in the art, the FC40 electronic fluorinated fluid (also known as FC-40, 3M Fluorinert electronic fluorinated fluid) in this solution is a perfluorocarbon compound produced by 3M and is mainly used for cooling and cleaning electronic equipment.

[0008] As is readily understood, the nanoparticles in this invention can undergo surface modification treatment. For example, the nanoparticles are typically dispersed in a solvent, a coupling agent is added, the mixture is stirred and reacted at a certain temperature, and then washed and dried. Vapor deposition can also be used.

[0009] As a further improvement of the present invention, the polar organic solvent is composed of n-propanol and FC40 electronic fluorinated liquid in a mass ratio of 1:1.1 to 1.8.

[0010] The fluoropolymers used in this invention may be selected from one or more of perfluoroethylene ether, soluble polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, polytetrafluoroethylene, CYTOP, LUMIFLON, Nafion NR40, Viton GLT-S, Viton ETP-S, ECCtreme ECA, and Teflon AF.

[0011] As will be readily understood by those skilled in the art, Teflon AF (also known as AF) in this solution is an amorphous fluoropolymer developed by Chemours (now DuPont), which is copolymerized from 2,2-bis(trifluoromethyl)-4,5-difluoro-1,3-dioxane-pentene and tetrafluoroethylene.

[0012] As a further improvement of the present invention, the fluoropolymer is composed of perfluorovinyl ether and Teflon AF in a mass ratio of 1:0.3 to 0.7.

[0013] In this invention, the dispersant may be selected from one or any of the following: ethylhexyl phosphate, sodium dodecyl sulfate, methyl pentanol, cellulose derivatives, polyacrylamide, glucon, fatty acid polyethylene glycol ester, HY512, and Ultra PX 4290; the nanoparticles may be selected from one or any of the following: nano silica, nano titanium dioxide, nano carbon black particles, multi-walled carbon nanotubes, and nano graphene.

[0014] To enable those skilled in the art to better implement this invention, we provide a preferred preparation method, which can be implemented according to the following steps:

[0015] S1. Take the quantities of each component according to the production raw material formula;

[0016] S2. Take a portion of the polar organic solvent and dissolve the fluoropolymer therein to obtain a mixed solution X;

[0017] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly to obtain a mixed solution Y;

[0018] S4. Mix the mixed solution X and the mixed solution Y under ultrasonic conditions to obtain a coating composition.

[0019] In step S4, the ultrasonic conditions can be: ultrasonic time of 3.5 to 4 minutes, with a magnetic field of intensity of 0.02 to 0.03 T applied simultaneously. Microfluidic mixing can be used, with the mixing ratio of the two mixed solutions being precisely controlled by a microfluidic chip to be 1:1.1 to 1.3 and the mixing path, to ensure that each component is uniformly dispersed at the microscopic level and to form a more stable mixed solution.

[0020] Step S2 can be performed by ultrasonic oscillation under high-speed stirring, with a stirring rate of 1400-1600 r / min and an ultrasonic oscillation frequency of 35-45 kHz. During the mixing process, light with a wavelength of 360-370 nm is introduced into the mixing system, and the mixing time is 1.5-2 minutes. This method can promote photochemical reaction between the fluorinated resin material and the solvent, forming a more stable bond state.

[0021] Step S3 can be performed by ultrasonic oscillation under high-speed stirring, with a stirring rate of 1100-1300 r / min and an ultrasonic oscillation frequency of 45-55 kHz. During the mixing process, a high-frequency alternating magnetic field with an intensity of 0.04-0.06 T is applied to the mixing system, causing the nanoparticles to vibrate under the action of the magnetic field. The mixing time is 6-8 minutes.

[0022] The present invention also discloses a superhydrophobic triboelectric durable coating composition, which is prepared by the method of the present invention for preparing a room temperature sprayable superhydrophobic triboelectric durable coating composition.

[0023] To enable those skilled in the art to better utilize this invention, we also disclose a method for using the above-mentioned superhydrophobic triboelectric durable coating composition. Those skilled in the art can use it according to the following method:

[0024] A. Clean the surface to be sprayed;

[0025] B. The superhydrophobic triboelectric durable coating composition is sprayed using a high-pressure airless spray gun with a spraying air pressure of 0.5-0.6 MPa, an electric field strength of 4500-5500 V / m, and a spray gun moving speed of 0.3-0.4 m / s.

[0026] C. The sprayed sample is placed in a room temperature and pressure environment with a humidity of 40% to 50% RH for curing.

[0027] During the spraying process, 3D scanning technology can be used to monitor changes in the shape and size of the substrate in real time. The intelligent control system can automatically adjust the moving speed and spraying angle of the spray gun to ensure the continuity and coverage of the coating.

[0028] The above surface treatment can be achieved by combining ultrasonic cleaning with acetone cleaning to ensure that the surface is free of oil, impurities, and contaminants, and then using plasma cleaning equipment for further treatment.

[0029] During the spraying process described above, 3D scanning technology can be used to monitor changes in the shape and size of the substrate in real time. An intelligent control system automatically adjusts the spray gun's movement speed and spraying angle to ensure coating continuity and coverage. Furthermore, the amount of mixed liquid can be precisely controlled based on the surface area of ​​the substrate to be sprayed, ensuring coating quality while avoiding material waste. Weight and flow sensors are used to monitor the amount of mixed liquid in real time, and a feedback control system automatically adjusts the spraying parameters.

[0030] During the curing process described above, microwave radiation technology can be introduced. For example, the microwave power can be set to 500W. Microwaves can accelerate the movement of molecules and cross-linking reactions within the coating.

[0031] The beneficial effects of this invention are: 1) Experiments show that the superhydrophobic triboelectric durable coating composition prepared by the method of this invention can significantly improve the triboelectric properties and superhydrophobicity of the electrically durable coating formed by spraying. 2) This invention uses a high-pressure airless spray gun in conjunction with an electric field to improve the spraying effect through electrostatic adsorption. Combined with 3D scanning and intelligent control, it ensures coating quality, precisely controls the dosage to avoid waste, stabilizes temperature and humidity, and combines microwave radiation to improve coating performance, shorten curing time, and improve production efficiency. It is easy to operate, has clear parameters, and is easy to control and scale up production. 3) This invention uses a combination of ultrasonic and acetone cleaning to remove impurities. Plasma equipment combined with a 50kHz pulsed electric field enhances coating adhesion. During the preparation of the two mixed solutions, stirring, ultrasonication, photocatalysis, and magnetic field assistance are used to ensure uniform dispersion of materials. A variety of materials can be selected to meet different needs. Ultrasonic and magnetic field-assisted mixing, combined with microfluidic technology for precise control, improves the stability of the mixed solution. Attached Figure Description

[0032] Figure 1 This is a process flow diagram of the specific implementation method.

[0033] Figure 2 The images show the coating state of the coating composition of Example 1 after being sprayed onto a glass substrate with different thicknesses and allowed to dry naturally for 90 seconds.

[0034] Figure 3 This is a SEM image of glass-based coating sample 1 in a specific embodiment.

[0035] Figure 4 This is an image showing the adhesion state of the coating composition of Example 1 on different surfaces.

[0036] Figure 5 These are SEM images of the coating composition of Example 1 on different surfaces, showing its adhesion state. Detailed Implementation

[0037] The present invention will be further described below with reference to embodiments.

[0038] Example 1:

[0039] The superhydrophobic triboelectric durable coating composition was prepared according to the following steps:

[0040] S1. Prepare the production raw material formula according to the mass ratio of polar organic solvent (n-propanol) to active ingredient of 8:1; wherein the active ingredient consists of fluoropolymer (perfluorovinyl ether), nanoparticles (nano silica) and dispersant (ethylhexyl phosphate); the mass ratio of fluoropolymer to modified nanoparticles is 10:1; the dispersant accounts for 1% of the mass of the active ingredient.

[0041] S2. Take 40% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1500 r / min and an ultrasonic oscillation frequency of 40 kHz. During the mixing process, light with a wavelength of 365 nm is introduced into the mixing system. The mixing time is 1.8 minutes to obtain mixed solution X.

[0042] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1200 r / min and an ultrasonic oscillation frequency of 50 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.05 T to the mixing system and mix for 7 minutes to obtain a mixed solution Y.

[0043] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.2 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.8 minutes, while a magnetic field with an intensity of 0.025T is applied to obtain the coating composition.

[0044] Example 2:

[0045] The superhydrophobic triboelectric durable coating composition was prepared according to the following steps:

[0046] S1. Prepare the production raw material formula according to the mass ratio of polar organic solvent (ethyl acetate) to active ingredient of 10:1; wherein the active ingredient is composed of fluoropolymer (polytetrafluoroethylene), nanoparticles (nano titanium dioxide) and dispersant (sodium dodecyl sulfate); the mass ratio of fluoropolymer to modified nanoparticles is 12:1; the dispersant accounts for 1.2% of the mass of active ingredient.

[0047] S2. Take 35% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1450 r / min and an ultrasonic oscillation frequency of 45 kHz. During the mixing process, light with a wavelength of 370 nm is introduced into the mixing system. The mixing time is 2 minutes to obtain mixed solution X.

[0048] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1300 r / min and an ultrasonic oscillation frequency of 55 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.045 T to the mixing system and mix for 6 minutes to obtain a mixed solution Y.

[0049] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.3 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.6 minutes, while a magnetic field with an intensity of 0.023T is applied to obtain the coating composition.

[0050] Example 3:

[0051] The superhydrophobic triboelectric durable coating composition was prepared according to the following steps:

[0052] S1. Prepare the production raw material formula according to the mass ratio of polar organic solvent (N,N-dimethylformamide) to active ingredient of 7:1; wherein the active ingredient consists of fluoropolymer (LUMIFLON), nanoparticles (multi-walled carbon nanotubes) and dispersant (Ultra PX 4290); the mass ratio of fluoropolymer to modified nanoparticles is 9:1; the dispersant accounts for 0.8% of the mass of active ingredient.

[0053] S2. Take 45% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1450 r / min and an ultrasonic oscillation frequency of 35 kHz. During the mixing process, light with a wavelength of 360 nm is introduced into the mixing system. The mixing time is 1.6 minutes to obtain mixed solution X.

[0054] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1250 r / min and an ultrasonic oscillation frequency of 55 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.055 T to the mixing system and mix for 6 minutes to obtain a mixed solution Y.

[0055] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.1 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.7 minutes, while a magnetic field with an intensity of 0.026T is applied to obtain the coating composition.

[0056] Example 4:

[0057] This example is a control experiment of Example 1, conducted according to the same steps and conditions as Example 1, using the same batch of raw materials. The difference lies in that the polar organic solvent is composed of n-propanol and FC40 electronic fluorinated liquid in a mass ratio of 1:1.5, while maintaining the total proportion of polar organic solvent used unchanged. The specific scheme is as follows:

[0058] S1. Prepare a production raw material formula according to a polar organic solvent (composed of n-propanol and FC40 electronic fluorinated liquid in a mass ratio of 1:1.5) to the effective ingredient in a mass ratio of 8:1; wherein the effective ingredient consists of a fluoropolymer (perfluorovinyl ether), nanoparticles (nano silica), and a dispersant (ethylhexyl phosphate); the mass ratio of the fluoropolymer to the modified nanoparticles is 10:1; the dispersant accounts for 1% of the mass of the effective ingredient.

[0059] S2. Take 40% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1500 r / min and an ultrasonic oscillation frequency of 40 kHz. During the mixing process, light with a wavelength of 365 nm is introduced into the mixing system. The mixing time is 1.8 minutes to obtain mixed solution X.

[0060] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1200 r / min and an ultrasonic oscillation frequency of 50 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.05 T to the mixing system and mix for 7 minutes to obtain a mixed solution Y.

[0061] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.2 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.8 minutes, while a magnetic field with an intensity of 0.025T is applied to obtain the coating composition.

[0062] Example 5:

[0063] This example is a control experiment of Example 1, conducted according to the same steps and conditions as Example 1, using the same batch of raw materials. The difference lies in that all polar organic solvents used are FC40 electronic fluorinated liquid, and the total proportion of polar organic solvents used remains unchanged. The specific scheme is as follows:

[0064] S1. Prepare the production raw material formula according to the mass ratio of polar organic solvent (FC40 electronic fluorinated liquid) to active ingredient of 8:1; wherein the active ingredient is composed of fluoropolymer (perfluorovinyl ether), nanoparticles (nano silica) and dispersant (ethylhexyl phosphate); the mass ratio of fluoropolymer to modified nanoparticles is 10:1; the dispersant accounts for 1% of the mass of the active ingredient.

[0065] S2. Take 40% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1500 r / min and an ultrasonic oscillation frequency of 40 kHz. During the mixing process, light with a wavelength of 365 nm is introduced into the mixing system. The mixing time is 1.8 minutes to obtain mixed solution X.

[0066] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1200 r / min and an ultrasonic oscillation frequency of 50 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.05 T to the mixing system and mix for 7 minutes to obtain a mixed solution Y.

[0067] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.2 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.8 minutes, while a magnetic field with an intensity of 0.025T is applied to obtain the coating composition.

[0068] Example 6:

[0069] This embodiment serves as a control experiment for Example 1, conducted according to the same steps and conditions, using the same batch of raw materials. The difference lies in that the fluoropolymer is composed of perfluorovinyl ether and Teflon AF in a mass ratio of 1:0.5, while maintaining the same total proportion of the fluoropolymer. The specific scheme is as follows:

[0070] S1. Prepare the production raw material formula according to the mass ratio of polar organic solvent (n-propanol) to active ingredient of 8:1; wherein the active ingredient consists of fluoropolymer (composed of perfluorovinyl ether and Teflon AF in a mass ratio of 1:0.5), nanoparticles (nano silica) and dispersant (ethylhexyl phosphate); the mass ratio of fluoropolymer to modified nanoparticles is 10:1; the dispersant accounts for 1% of the mass of the active ingredient.

[0071] S2. Take 40% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1500 r / min and an ultrasonic oscillation frequency of 40 kHz. During the mixing process, light with a wavelength of 365 nm is introduced into the mixing system. The mixing time is 1.8 minutes to obtain mixed solution X.

[0072] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1200 r / min and an ultrasonic oscillation frequency of 50 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.05 T to the mixing system and mix for 7 minutes to obtain a mixed solution Y.

[0073] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.2 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.8 minutes, while a magnetic field with an intensity of 0.025T is applied to obtain the coating composition.

[0074] Example 7:

[0075] This embodiment is a control experiment of Example 1, carried out according to the same steps and conditions as Example 1, and the raw materials used are from the same batch as in Example 1. The difference is that all the fluoropolymers are Teflon AF, and the total proportion of fluoropolymers used remains unchanged. The specific scheme is as follows:

[0076] S1. Prepare the production raw material formula according to the mass ratio of polar organic solvent (n-propanol) to active ingredient of 8:1; wherein the active ingredient consists of fluoropolymer (Teflon AF), nanoparticles (nano silica) and dispersant (ethylhexyl phosphate); the mass ratio of fluoropolymer to modified nanoparticles is 10:1; the dispersant accounts for 1% of the mass of the active ingredient.

[0077] S2. Take 40% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1500 r / min and an ultrasonic oscillation frequency of 40 kHz. During the mixing process, light with a wavelength of 365 nm is introduced into the mixing system. The mixing time is 1.8 minutes to obtain mixed solution X.

[0078] S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1200 r / min and an ultrasonic oscillation frequency of 50 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.05 T to the mixing system and mix for 7 minutes to obtain a mixed solution Y.

[0079] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.2 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.8 minutes, while a magnetic field with an intensity of 0.025T is applied to obtain the coating composition.

[0080] Comparative Example 1:

[0081] This comparative example serves as a control experiment for Example 1, conducted according to the same steps and conditions as Example 1, using the same batch of raw materials. The difference lies in the absence of nanoparticles. The specific scheme is as follows:

[0082] S1. Prepare the production raw material formula according to the mass ratio of polar organic solvent (n-propanol) to active ingredient of 8:1; wherein the active ingredient is composed of fluoropolymer (perfluorovinyl ether) and dispersant (ethylhexyl phosphate); the dispersant accounts for 1% of the mass of the active ingredient.

[0083] S2. Take 40% of the polar organic solvent and dissolve the fluoropolymer in it. Mix the mixture by ultrasonic oscillation under high-speed stirring at a stirring rate of 1500 r / min and an ultrasonic oscillation frequency of 40 kHz. During the mixing process, light with a wavelength of 365 nm is introduced into the mixing system. The mixing time is 1.8 minutes to obtain mixed solution X.

[0084] S3. Add the dispersant to the remaining polar organic solvent and mix evenly. Mix by ultrasonic oscillation under high-speed stirring at a stirring rate of 1200 r / min and an ultrasonic oscillation frequency of 50 kHz. During the mixing process, apply a high-frequency alternating magnetic field with an intensity of 0.05 T to the mixing system and mix for 7 minutes to obtain a mixed solution Y.

[0085] S4. Using a microfluidic mixing method, the mixing ratio of the two mixed solutions is precisely controlled to be 1:1.2 by a microfluidic chip. The mixed solution X and the mixed solution Y are mixed under ultrasonic conditions for 3.8 minutes, while a magnetic field with an intensity of 0.025T is applied to obtain the coating composition.

[0086] Comparative experiment on the triboelectric properties and superhydrophobicity of coating compositions:

[0087] I. Preparation of Coating Samples:

[0088] The coating compositions prepared in each of the above embodiments and comparative examples were respectively subjected to surface spraying to obtain electrically durable coating samples according to the following steps:

[0089] (1) Eight identical glass substrates (size 50mm×50mm, initial contact angle 35±2°, no sliding angle) and eight identical copper film substrates (size 50mm×50mm, initial contact angle 67±2°, no sliding angle) were subjected to surface deep cleaning. The method of ultrasonic cleaning for 15 minutes and chemical reagent acetone cleaning for 10 minutes was combined to ensure that the surface was free of oil, impurities and contaminants. Then, the pulse electric field plasma cleaning equipment was used for treatment. The pulse electric field frequency was set to 50kHz and the treatment time was set to 8 minutes.

[0090] (2) The coating compositions of the above embodiments and comparative examples were sprayed onto glass substrates and copper film substrates respectively using a high-pressure airless spray gun. Each glass substrate and copper film substrate was sprayed with one composition. The spraying air pressure was 0.55 MPa and the electric field strength was 5000 V / m. During the spraying process, the sprayed composition solution was charged. Using the principle of electrostatic adsorption, the composition solution was made to adhere more tightly to the surface of the glass substrate and the copper film substrate. The spray gun moving speed was 0.35 m / s to ensure that a continuous and uniform coating was formed on the substrate.

[0091] (3) After spraying, the sample was placed at room temperature and pressure and cured by microwave radiation in a specific humidity environment of 45%RH (microwave power set to 500W). Examples 1, 2, 3, 4, 5, 6, 7, and Comparative Example 1 respectively obtained glass-based coating sample 1, glass-based coating sample 2, glass-based coating sample 3, glass-based coating sample 4, glass-based coating sample 5, glass-based coating sample 6, glass-based coating sample 7, glass-based coating sample D1 and copper film-based coating sample 1, copper film-based coating sample 2, copper film-based coating sample 3, copper film-based coating sample 4, copper film-based coating sample 5, copper film-based coating sample 6, copper film-based coating sample 7, copper film-based coating sample D1.

[0092] II. Testing of sample triboelectricity and superhydrophobicity:

[0093] (a) Triboelectric property testing:

[0094] The copper film-based coating samples 1, 2, 3, 4, 5, 6, 7, and D1 were subjected to a comparative test of their triboelectric properties using the following method:

[0095] 1. Prepare electrode leads: Take a short section of copper wire and carefully strip the insulation layer from one end.

[0096] 2. Apply conductive adhesive: Apply a small amount of conductive adhesive to the edge of the uncoated side (i.e., the copper film substrate) of the sample to be tested.

[0097] 3. Connect the electrode leads: Firmly attach the ends of the copper wires (with the insulation layer removed) to the conductive adhesive to ensure good and stable electrical contact between the wires and the copper film substrate.

[0098] 4. Curing the conductive adhesive: Place the sample with the leads connected horizontally in a fume hood or drying oven, and allow it to cure (1 hour at room temperature) according to the product specifications of the conductive adhesive used, until the conductive adhesive is completely dry.

[0099] 5. Apply insulating tape: Apply insulating double-sided tape to the uncoated side (back) of the sample for subsequent fixation.

[0100] 6. Secure the sample: Secure the sample, with the insulating double-sided tape applied, horizontally and firmly onto the base of the optical platform. Ensure the sample does not shift during the experiment.

[0101] 7. Connect the sample to the electrometer: Connect the copper wire leading from the sample to the positive (red) input terminal of the electrometer (Keithley 6514).

[0102] 8. Electrometer grounding: Connect the negative (black) input terminal of the electrometer to the common ground using a grounding wire.

[0103] 9. Connect the data acquisition card: Connect the signal output terminal of the electrometer to the corresponding input channel of the data acquisition card (NI PCI-6255).

[0104] 10. Install the moving electrode: Securely fix a 50mm × 50mm copper film to the moving end of the linear motor, adjust its position to ensure that its surface is flat and strictly parallel to the surface of the fixed sample coating.

[0105] 11. Start and configure the software: Start the LabVIEW data acquisition program on the computer, set the sampling frequency of the data acquisition card to 1kHz, and configure the data recording channel and file storage path.

[0106] 12. Set the linear motor parameters: On the motor controller, set the motion mode to reciprocating motion, the motion frequency to 1Hz, and the maximum separation distance (stroke) to 3cm.

[0107] 13. Calibrate the initial position: Precisely adjust the initial position of the linear motor so that the copper film at the moving end just contacts the sample coating surface. Use the resistance setting of a multimeter to assist in this process to ensure consistent starting conditions for each experiment.

[0108] 14. Measuring Open Circuit Voltage (VOC): Set the electrometer (Keithley 6514) to Voltage Mode, then simultaneously start the linear motor and the LabVIEW data acquisition program. After the output signal stabilizes (approximately 20-30 cycles), continuously record the voltage-time curve for at least 10 cycles. After the measurement is complete, select several stable peak voltages from the recorded data, calculate their average value, and use this average value as the VOC of the sample.

[0109] 15. Measuring Short-Circuit Current (ISC): First, stop the linear motor and data acquisition. Then, switch the electrometer (Keithley 6514) to Current Mode. Restart the linear motor and LabVIEW data acquisition program. After the output signal stabilizes, continuously record at least 10 cycles of current-time data. After the measurement is complete, read the positive and negative peak currents from the recorded data for multiple cycles, calculate their average absolute value, and use this as the ISC of the sample.

[0110] 16. Change the sample and repeat the measurement: After completing the measurement of one sample, stop all equipment. Carefully remove the measured sample and replace it with the next sample to be tested (sample 2, 3...D1), and strictly repeat all operations from steps 1 to 15.

[0111] 17. Organize and record data: After all samples have been tested, systematically record the average value of each sample in Table 1.

[0112] (II) Superhydrophobicity test:

[0113] The superhydrophobicity comparison test was conducted on the glass-based coating samples 1, 2, 3, 4, 5, 6, 7, and D1 according to the following method:

[0114] 1. Instrument power-on and warm-up: Start the contact angle meter and its matching light source and camera, and warm up for 20 minutes according to the equipment operation requirements to ensure that the entire testing system is in a stable state.

[0115] 2. Leveling the sample stage: Use the instrument's built-in level or place a high-precision level on the sample stage and adjust the leveling feet at the bottom of the platform until the sample stage is completely level.

[0116] 3. Calibrate the measurement software: Open the contact angle measurement software and adjust the camera's focal length, light source brightness, and image contrast according to the actual situation to ensure that the outline of the droplet can be clearly observed on the screen.

[0117] 4. Sample preparation and placement: Gently blow the surface of the sample to be tested with a nitrogen gun to remove any possible dust, and then place it stably on the leveled contact angle meter sample stage.

[0118] 5. Adding the test droplet: Accurately draw 10 µL of ultrapure water using a pipette. Hold the pipette perpendicular to the sample surface, bringing the tip as close to the surface as possible, and then slowly and steadily release the water droplet into the center of the coating surface. This operation should be gentle to avoid affecting the natural spreading pattern of the droplet due to excessive impact.

[0119] 6. Measuring the contact angle (CA): Immediately after the droplet contacts and stabilizes with the sample surface, capture the lateral profile image of the droplet. Then, analyze the image using the software's built-in tangent method or Young-Laplace fitting method to measure the angle between the droplet and the solid surface at the three-phase contact point. Record the contact angles on the left and right sides respectively, and calculate their average value as the contact angle (CA) value for that measurement point.

[0120] 7. Measurement of Roll-Off Angle (SA): After completing the contact angle measurement, directly use the same droplet on the sample surface to measure the roll-off angle. Activate the tilt function of the sample stage and begin tilting the platform at a slow and constant rate (1 degree / second). Closely observe the droplet through the camera system. The instant the three-phase contact line of the droplet begins to shift significantly (i.e., the droplet is about to roll or has already begun to roll), immediately record the tilt angle of the platform at this moment. This angle is the roll-off angle (SA).

[0121] 8. Perform repeated measurements: For the same coated sample, repeat the measurement process of steps 4 to 7 above completely at at least 5 different locations (or 10 different locations according to the original experimental requirements), that is, each time add a brand new 10µL drop at a new location and measure its contact angle and roll-off angle in turn.

[0122] 9. Change the sample: After all repeated measurements of a sample are completed, replace it with the next sample to be tested, and repeat all the operation procedures from steps 4 to 8.

[0123] 10. Organize and record data: After all samples have been tested, calculate the arithmetic mean of the contact angle (CA) and roll-off angle (SA) of each sample for 10 measurements, and record the final results in Table 1.

[0124] Table 1. Results of triboelectric properties and superhydrophobicity of coated samples

[0125] sample Surface contact angle Slide angle sample Open circuit voltage (V) Short-circuit current (nA) Glass-based coating sample 1 158° 5.2° Copper film-based coating sample 1 98 420 Glass-based coating sample 2 157° 5.1° Copper film-based coating sample 2 102 432 Glass-based coating sample 3 157° 5.2° Copper film base coating sample 3 97 461 Glass-based coating sample 4 (n-propanol + FC40) 164° 2.9° Copper film-based coating sample 4 (n-propanol + FC40) 110 503 Glass-based coating sample 5 156° 4.8° Copper film base coating sample 5 88 384 Glass-based coating sample 6 (perfluorovinyl ether + Teflon AF) 159° 5.1° Copper film-based coating sample 6 (perfluorovinyl ether + Teflon AF) 134 587 Glass-based coating sample 7 158° 5.0° Copper film-based coating sample 7 112 514 Glass-based coating sample D1 120° none Copper film-based coating sample D1 76 320

[0126] The test results of glass-based coating samples 1 to 7 in Table 1 show that the contact angle of the glass-based coating surface formed by the coating composition produced by the method of the present invention is stable above 156°, while the sliding angle is stable below 5.1°, indicating that the coating formed by the coating composition produced by the method of the present invention has excellent superhydrophobicity.

[0127] The test results of copper film-based coating samples 1 to 7 in Table 1 show that the open-circuit voltage of the copper film-based coating formed by the coating composition produced by the method of the present invention is stable above 88V, and can even reach 134V; the short-circuit current is stable above 384nA, and can even reach 587nA; it can be seen that the coating formed by the coating composition produced by the method of the present invention has excellent triboelectric properties.

[0128] The comparison of the test results of copper film-based coating sample 1 and copper film-based coating sample D1 in Table 1 shows that the triboelectric properties of coating sample 1 are significantly better than those of coating sample D1, indicating that the present invention plays a key role in providing surface roughness and enhancing triboelectric properties by using nanoparticle materials.

[0129] A comparison of the test results of glass-based substrate sample 1, glass-based coating sample 4, and glass-based coating sample 5 in Table 1 shows that, under the premise that the total proportion of polar organic solvents used is exactly the same, the contact angle and sliding angle of the coating surface formed by the composition of Example 1, which uses n-propanol alone as a polar organic solvent, are 158° and 5.2°, respectively. The contact angle and sliding angle of the coating surface formed by the composition of Example 5, which uses FC40 electronic fluorinated liquid alone as a polar organic solvent, are 156° and 4.8°, respectively. The corresponding values ​​of the coating formed by Example 4, which uses a composite polar organic solvent composed of n-propanol and FC40 electronic fluorinated liquid, are 164° and 2.9°, respectively, which are significantly better than the effects of using n-propanol and FC40 electronic fluorinated liquid alone. The inventors believe that the reason is that after n-propanol and FC40 electronic fluorinated liquid are mixed and sprayed, they can interact to form a denser rough structure, thereby synergistically improving the superhydrophobicity of the coating.

[0130] A comparison of the test results for copper film-based coating samples 1, 6, and 7 in Table 1 shows that, under the premise that the total proportion of fluoropolymers used is exactly the same, the open-circuit voltage and short-circuit current of the coating formed by using perfluorovinyl ether alone in Example 1 are 98V and 420nA, respectively; the open-circuit voltage and short-circuit current of the coating formed by using Teflon AF alone in Example 7 are 112V and 514nA, respectively; while the corresponding values ​​of the coating formed by using the composite fluoropolymer of perfluorovinyl ether and Teflon AF in Example 6 are 134V and 587nA, respectively. The triboelectric properties are significantly better than those achieved by using perfluorovinyl ether or Teflon AF alone. The inventors believe that this may be because the composite fluoropolymer formed by perfluorovinyl ether and Teflon AF provides a more complete and robust coating of nanoparticles, thereby synergistically improving the triboelectric properties of the coating.

Claims

1. A method for preparing a room-temperature sprayable superhydrophobic triboelectric durable coating composition, characterized in that: The raw material formulation includes an active ingredient and a polar organic solvent, wherein the mass ratio of the polar organic solvent to the active ingredient is 6–10:1; the active ingredient includes a fluoropolymer, nanoparticles, and a dispersant; the mass ratio of the fluoropolymer to the nanoparticles is 8–12:1; and the dispersant accounts for 0.5%–1.5% of the mass of the active ingredient.

2. The method for preparing the room-temperature sprayable superhydrophobic triboelectric durable coating composition according to claim 1, characterized in that: The polar organic solvent is selected from one or any combination of ethyl acetate, acetone, ethanol, FC40 electronic fluorinated liquid, n-propanol, methyl isobutyl ketone, N,N-dimethylformamide, methyl ethyl ketone, and xylene.

3. The method for preparing the room-temperature sprayable superhydrophobic triboelectric durable coating composition according to claim 2, characterized in that: The polar organic solvent is composed of n-propanol and FC40 electronic fluorinated liquid in a mass ratio of 1:1.1 to 1.

8.

4. The method for preparing the room-temperature sprayable superhydrophobic triboelectric durable coating composition according to claim 1, characterized in that: The fluoropolymer is selected from one or more of perfluoroethylene ether, soluble polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, polytetrafluoroethylene, CYTOP, LUMIFLON, Nafion NR40, Viton GLT-S, Viton ETP-S, ECCtreme ECA, and Teflon AF.

5. The method for preparing the room-temperature sprayable superhydrophobic triboelectric durable coating composition according to claim 4, characterized in that: The fluoropolymer is composed of perfluorovinyl ether and Teflon AF in a mass ratio of 1:0.3 to 0.

7.

6. The method for preparing the room-temperature sprayable superhydrophobic triboelectric durable coating composition according to claim 1, characterized in that: The dispersant is selected from one or more of ethylhexyl phosphate, sodium dodecyl sulfate, methyl pentanol, cellulose derivatives, polyacrylamide, glucon, fatty acid polyethylene glycol ester, HY512, and Ultra PX 4290; the nanoparticles are selected from one or more of nano silica, nano titanium dioxide, nano carbon black particles, multi-walled carbon nanotubes, and nano graphene.

7. The method for preparing the room-temperature sprayable superhydrophobic triboelectric durable coating composition according to any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Take the quantities of each component according to the production raw material formula; S2. Take a portion of the polar organic solvent and dissolve the fluoropolymer therein to obtain a mixed solution X; S3. Add the nanoparticles and dispersant to the remaining polar organic solvent and mix evenly to obtain a mixed solution Y; S4. Mix the mixed solution X and the mixed solution Y under ultrasonic conditions to obtain a coating composition.

8. The method for preparing the room-temperature sprayable superhydrophobic triboelectric durable coating composition according to claim 7, characterized in that: In step S4, the ultrasonic conditions are as follows: ultrasonic time 3.5–4 minutes, with a magnetic field of intensity 0.02–0.03T applied simultaneously; in step S2, ultrasonic oscillation is performed under high-speed stirring at a stirring rate of 1400–1600 r / min and an ultrasonic oscillation frequency of 35–45 kHz. During the mixing process, light with a wavelength of 360–370 nm is introduced into the mixing system, and the mixing time is 1.5–2 minutes; in step S3, ultrasonic oscillation is performed under high-speed stirring at a stirring rate of 1100–1300 r / min and an ultrasonic oscillation frequency of 45–55 kHz. During the mixing process, a high-frequency alternating magnetic field of intensity 0.04–0.06T is applied to the mixing system, and the mixing time is 6–8 minutes; in step S4, microfluidic mixing is used, and the flow ratio of the mixed solution X to the mixed solution Y is 1:1.1–1.

3.

9. A superhydrophobic triboelectric durable coating composition prepared by the method of preparing a room temperature sprayable superhydrophobic triboelectric durable coating composition according to any one of claims 1 to 8.

10. A method of using the superhydrophobic triboelectric durable coating composition of claim 9, comprising the following steps: A. Clean the surface to be sprayed; B. The superhydrophobic triboelectric durable coating composition is sprayed using a high-pressure airless spray gun with a spraying air pressure of 0.5-0.6 MPa, an electric field strength of 4500-5500 V / m, and a spray gun moving speed of 0.3-0.4 m / s. C. The sprayed sample is placed in a room temperature and pressure environment with a humidity of 40% to 50% RH for curing.